FILSAFAT AL-NAFS, FISAFAT KENABIAN, FILSAFAT AL-MADINAH, FILSAFAT AL-FADILAH DALAM PANDANGAN AL-FARABI (Suatu Kajian Terhadap Pokok-Pokok Fisafatnya) - Ahmad Badwi (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
This article outlines the problems of Al-Nafs Philosophy, Prophetic Philosophy, Al-Madinah Philosophy, Al-Fadilah Philosophy in Al-Farabi's View (A Study of the Basics of His Philosophy). From the results of the study obtained an understanding that the thoughts of al-Farabi adopted a lot of Greek thinkers, especially Aristotle, Plato, and Neo-Platonism. However, with a strong foundation of Islamic religion, al-Farabi can produce a new thought and theories to add to the scientific treasures in the Islamic world, so that with his fame, the theories he developed were also absorbed by many Western scientists. Al-Farabi is the oldest source of Sufism and philosophical thought among Islamic philosophers. Al-Farabi's thoughts about al-Nasf how the soul can live happily both in the world and the hereafter and likewise about al-Farabi's prophecy try to explain that the Prophet and the philosophers are different and therefore explain in detail as discussed above, and also with the main country that al-Farabi described as this body will work in accordance with the functions and duties of each to achieve happiness in life.